Perioperative inflammation as triggering oigin of metastasis development - Retsky, Michael W.; Demicheli, Romano (Springer, 2017)
The book will explain previously unconnected clinical data such as why mammography works better for women age 50-59 than it does for women age 40-49, why adjuvant chemotherapy works best for premenopausal patients with positive lymph nodes, and it may also explain the racial disparity in outcome. In particular, it points to the perioperative period when systemic inflammation persists for a week or so. This can lead to a variety of mechanisms whereby single cancer cells (perhaps from the marrow) begin division and angiogenesis of dormant avascular micrometastases occurs leading to early relapses. With chapters presented from distinguished scientists and physicians in a variety of specialties that relate to and border the effects we present, this volume can be used as a reference for practicing physicians and as a jumping-off point for researchers to explore new therapeutic opportunities.
Keywords: Breast -- Cancer.; Breast -- Radiography.; Inflammation.; Metastasis.; elektronické knihy; electronic books